Leaf architecture and ecophysiology of an early basal eudicot from the Early Cretaceous of Spain. (December 2013) - Barral, Abel; Gomez, Bernard; Feild, Taylor S.; Coiffard, Clément; Daviero‐Gomez, Véronique
<x xml:space="preserve">Abstract</x> Iterophyllum lobatum gen. et sp. nov. is reported from the late Barremian lithographic limestones of Las Hoyas, Spain. It consists of a simple, petiolate leaf, with a pinnately lobed lamina. The dentate thickened margin bears chloranthoid‐like glands at lobe apices and sinuses. The venation is pinnate and craspedodromous, with three discernible vein orders. Based on the low regularity of vein course and angles and the low leaf rank, such a venation pattern may represent an early evolved leaf archetype in early basal eudicots. An acropetal leaf development mode in I. lobatum is similar to that in several living Papaveraceae. The leaf architecture and ecophysiology, particularly the vein widths and the glands, indicate that I. lobatum leaves were aerial. The plant grew close to water in the wetland terrestrial ecosystem of Las Hoyas. Iterophyllum lobatum might have been an opportunist species in early ecological succession stages after wildfires. © 2013 The Linnean Society of London, Botanical Journal of the Linnean Society, 2013, 173, 594–605.